The analysis of the key indicators of the Republic of Serbia banking sector - Ercegovac, Dajana; Vlaović-Begović, Sanja; Jovin, Slobodanka (Anali Ekonomskog fakulteta u Subotici, 2020)
The objective of the paper is to analyze development of Serbian banking sector, from troubled and insolvent public banking sector in the 1990s, through process of consolidation and privatization in 2000 until today’s stable and profitable banking sector with dominant foreign property of banks in Serbia. The subject of this research is analysis of the key indicators of banking sector in Serbia: profitability, liquidity, capital adequacy, leverage, exchange rate risk and default credits from 2010 until July 2018. Also, authors calculate share in total assets, share in total equity and profitability through ROA and ROE indicators for banks in Serbia divided by ownership in 2016 and 2017 on the base of data in the financial reports publicized on the NBS web site.